2020
DOI: 10.1136/bmjopen-2020-039105
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a double-blind, randomised placebo-controlled trial evaluating clinical effects of platelet-rich plasma injection for acute grade-2 hamstring tear among high performance athletes

Abstract: IntroductionHamstring injury among athletes often results in significant morbidity. Currently, there are controversies regarding the clinical use of platelet-rich plasma (PRP) for the treatment of acute hamstring injury.Methods and analysisThis study is a single-centre double-blind randomised placebo-controlled trial. Sixty-eight patients will be randomised to receive under ultrasound guidance either a single injection of leucocyte-rich PRP (LR-PRP) or normal saline. All patients will undergo a standardised ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…According to Orlandi et al, from 2 to 10 mL of PRP, and from one to three total injections, might be effective depending on the degree and extent of the lesion [61]. Several in vitro studies support the potential benefits of PRP in the treatment of muscle injuries [67,68], even if clinical studies reported conflicting results about the effectiveness of this procedure [69][70][71][72][73]. Setayesh et al in a recent review suggest that these uncertainties are probably attributable to the great heterogeneity in PRP formulations and treatment protocols [74].…”
Section: Rehabilitation and Interventional Therapymentioning
confidence: 99%
“…According to Orlandi et al, from 2 to 10 mL of PRP, and from one to three total injections, might be effective depending on the degree and extent of the lesion [61]. Several in vitro studies support the potential benefits of PRP in the treatment of muscle injuries [67,68], even if clinical studies reported conflicting results about the effectiveness of this procedure [69][70][71][72][73]. Setayesh et al in a recent review suggest that these uncertainties are probably attributable to the great heterogeneity in PRP formulations and treatment protocols [74].…”
Section: Rehabilitation and Interventional Therapymentioning
confidence: 99%